2023
DOI: 10.3390/brainsci13040632
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of the Anti-Inflammatory Effects of Epigallocatechin 3-Gallate (EGCG) in LPS-Activated BV-2 Microglia Cells

Abstract: Chronic neuroinflammation is associated with many neurodegenerative diseases, such as Alzheimer’s. Microglia are the brain’s primary immune cells, and when activated, they release various proinflammatory cytokines. Several natural compounds with anti-inflammatory and antioxidant properties, such as epigallocatechin 3-gallate (EGCG), may provide a promising strategy for inflammation-related neurodegenerative diseases involving activated microglia cells. The objective of the current study was to examine the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…A similar study reported that EGCG administration significantly inhibited IL-6, IL-8, VEGF, and PGE2 production, decreased COX-2 expression, and inhibited NF-κB activation, with subsequent inhibition of phosphorylation of p38, JNK, and ERK in IL-1β+Aβ (25-35) -induced U373MG cells [ 219 ]. Furthermore, in microglial BV-2 cells stimulated with LPS, pretreatment with EGCG significantly inhibited the production of the proinflammatory mediator NO, decreased the release of proinflammatory cytokine IL-6 while increasing TNF-α, downregulated MIF, CCL-2, and CSF2 and upregulated IL-3, IL-11, and TNFS10, significantly downregulated mTOR, NF-κB2, STAT1, Akt3, CCL5, and SMAD3 while significantly upregulating the expression of mRNA of Ins2, Pld2, A20/TNFAIP3, and GAB1 [ 220 ]. Similarly, EGCG is associated with protection against Aβ and LPS-induced neurotoxicity in SH-SY5Y and BV-2 microglial cells through the inhibition of proinflammatory cytokines (IL-1β and IL-18), the reduction in Iba-1 over-expression, and the suppression of the co-localization of caspase-1 and Iba-1 activation as shown by immunofluorescence staining.…”
Section: Dietary Small Molecules and Neuroprotection – A Overview Of ...mentioning
confidence: 99%
“…A similar study reported that EGCG administration significantly inhibited IL-6, IL-8, VEGF, and PGE2 production, decreased COX-2 expression, and inhibited NF-κB activation, with subsequent inhibition of phosphorylation of p38, JNK, and ERK in IL-1β+Aβ (25-35) -induced U373MG cells [ 219 ]. Furthermore, in microglial BV-2 cells stimulated with LPS, pretreatment with EGCG significantly inhibited the production of the proinflammatory mediator NO, decreased the release of proinflammatory cytokine IL-6 while increasing TNF-α, downregulated MIF, CCL-2, and CSF2 and upregulated IL-3, IL-11, and TNFS10, significantly downregulated mTOR, NF-κB2, STAT1, Akt3, CCL5, and SMAD3 while significantly upregulating the expression of mRNA of Ins2, Pld2, A20/TNFAIP3, and GAB1 [ 220 ]. Similarly, EGCG is associated with protection against Aβ and LPS-induced neurotoxicity in SH-SY5Y and BV-2 microglial cells through the inhibition of proinflammatory cytokines (IL-1β and IL-18), the reduction in Iba-1 over-expression, and the suppression of the co-localization of caspase-1 and Iba-1 activation as shown by immunofluorescence staining.…”
Section: Dietary Small Molecules and Neuroprotection – A Overview Of ...mentioning
confidence: 99%
“…EGCG possesses immunomodulatory properties, which can help regulate and balance the immune system's response. EGCG has been shown to inhibit the production of pro-inflammatory molecules, such as cytokines and chemokines, while promoting the production of anti-inflammatory substances [162]. Additionally, EGCG has been found to modulate immune cell function by enhancing the activity of natural killer (NK) cells, T cells, and B cells [163].…”
Section: Epigallocatechin Gallate (Egcg) and Green Tea Extract Consum...mentioning
confidence: 99%
“…Unlike green tea, black tea involves a fermentation process in its preparation, during which these phenolic compounds are oxidized to form new compounds, such as theobromine and theaflavin, thereby diminishing the EGCG content in black tea. EGCG exhibits a broad spectrum of biological activities, including hypoglycemic [1], antibacterial [2], antiviral [3], antioxidant [4], anti-atherosclerotic [5], antitumor [6] and anti-inflammatory [7] effects. Therefore, tea and its extract have been widely commercialized, commonly in the pharmaceutical, healthcare, and food industries [8][9][10].…”
Section: Introductionmentioning
confidence: 99%